The impact of international swap lines on stock returns of banks in emerging markets - Alin Marius Andrieș; Andreas M. Fischer; Pınar Yeșin (Swiss National Bank, Study Center Gerzensee, 2015)
This paper investigates the impact of international swap lines on stock returns using data from banks in emerging markets. The analysis shows that swap lines by the Swiss National Bank (SNB) had a positive impact on bank stocks in Central and Eastern Europe. It then highlights the importance of individual bank characteristics in identifying the impact of swap lines on bank stocks. Bank-level evidence suggests that stock prices of local and less-well capitalized banks as well as banks with high foreign currency exposures and high reliance on short-term funding responded more strongly to SNB swap lines. This new evidence is consistent with the view that swap lines not only enhanced market liquidity but also reduced risks associated with micro-prudential issues.
Keywords: F15; F21; F32; F36; G15; 330; swap lines; foreign currency loans; bank stocks; emerging markets; Swap; Internationale Anleihe; Zentralbank; Schweizerisch; Wirkungsanalyse; Bank; Börsenkurs; Kapitalmarktrendite; Schweiz; Osteuropa; Schwellenländer